The disruptive relationship among circadian rhythms, pain, and opioids - Bumgarner, Jacob R.; McCray, Evan W.; Nelson, Randy J. (Frontiers in Neuroscience, 2023)
Pain behavior and the systems that mediate opioid analgesia and opioid reward processing display circadian rhythms. Moreover, the pain system and opioid processing systems, including the mesolimbic reward circuitry, reciprocally interact with the circadian system. Recent work has demonstrated the disruptive relationship among these three systems. Disruption of circadian rhythms can exacerbate pain behavior and modulate opioid processing, and pain and opioids can influence circadian rhythms. In this review, we highlight evidence demonstrating the relationship among the circadian, pain, and opioid systems. We then review evidence of how disruption of one of these systems can lead to reciprocal disruptions of the other. The interconnected nature of these systems is then discussed to emphasize the importance of their interactions in therapeutic contexts.